2020
DOI: 10.1007/s11302-020-09735-w
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 is a cytotoxic receptor….maybe not: implications for cancer

Abstract: The tumor microenvironment is rich in extracellular ATP. This nucleotide affects both cancer and infiltrating immune cell responses by acting at P2 receptors, chiefly P2X7. ATP is then degraded to generate adenosine, a very powerful immunosuppressant. The purinergic hypothesis put forward by Geoff Burnstock prompted innovative investigation in this field and provided the intellectual framework to interpret a myriad of experimental findings. This is a short appraisal of how Geoff’s inspiration influenced cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…While the P2X 7 receptor was originally referred to as ''death receptor,'' more recent work indicates the contribution of the receptor is much more nuanced, with participation in a variety of signaling events; stimulation can even lead to a proliferation in microglial cells (Bianco et al, 2006). These varied outcomes from the P2X 7 receptor may be explained by differences in splice variant expression, agonist availability, and other factors still under investigation (Adinolfi et al, 2010;Di Virgilio, 2020). While excessive stimulation can lead to microglial cell death, the effects of the P2X 7 receptor on the endolysosomal axis discussed here usually do not lead to cellular demise but have sustained pathological consequences for microglial clearance instead.…”
Section: Extracellular Atp and P2x 7 Receptorsmentioning
confidence: 99%
“…While the P2X 7 receptor was originally referred to as ''death receptor,'' more recent work indicates the contribution of the receptor is much more nuanced, with participation in a variety of signaling events; stimulation can even lead to a proliferation in microglial cells (Bianco et al, 2006). These varied outcomes from the P2X 7 receptor may be explained by differences in splice variant expression, agonist availability, and other factors still under investigation (Adinolfi et al, 2010;Di Virgilio, 2020). While excessive stimulation can lead to microglial cell death, the effects of the P2X 7 receptor on the endolysosomal axis discussed here usually do not lead to cellular demise but have sustained pathological consequences for microglial clearance instead.…”
Section: Extracellular Atp and P2x 7 Receptorsmentioning
confidence: 99%
“…A very potent anti-P2X7 receptor, bivalent nanobody-Fc has also been developed and had beneficial effects in mouse models of allergic contact dermatitis and experimental glomerulonephritis [53]. P2X7 receptors are also expressed in numerous types of cancerous cell [52,54] and a recent phase 1 trial with an ointment containing an antibody, BIL010t, directed against the P2X7 receptor reduced the lesion area in 65% of patients with basal cell carcinoma [55]. An anti-P2X7R vaccine (BIL06v), is under assessment in patients with advanced solid tumours [52].…”
Section: P2x and P2y Receptors Todaymentioning
confidence: 99%
“…Many studies have proposed and demonstrated that eHSP90 can chaperone clients in an ATP independent manner ( Cheng et al, 2011 ; Sims et al, 2011 ; McCready et al, 2014 ), however Baker-Williams et al (2019) proved that eHSP90 needs ATP hydrolysis to properly fold MMP2. Since cells can actively secrete ATP in response to a variety of stressful stimuli ( Di Virgilio, 2021 ), it is possible that, at least in some contexts, eHSP90 binds, and hydrolases ATP to carry out its extracellular duties.…”
Section: Ehsp90 Complexes Remodel Tumor Microenvironmentmentioning
confidence: 99%